Potential activity of Pleurotus nebrodensis mushroom extract against biofilm of meticillin-resistant Staphylococcus aureus and Pseudomonas aeruginosa - Gargano, Maria Letizia; Cicero, Ilenia; Cirlincione, Fortunato; Giammanco, Anna; Talarico, Virginia; Arrigo, Ignazio; Fasciana, Teresa Maria Assunta (Frontiers in Bacteriology, 2025)
Mushroom extracts are a promising resource for treating bacterial infections associated with biofilms, offering a dual effect: inhibiting biofilm formation and facilitating infection healing. In this paper, after collecting in the wild basidiomes of P. nebrodensis, a rare and endangered species, we proceeded with the isolation of mycelium in pure culture. Preparation of the culture bags was entrusted to a leading fungiculture company. Cultivation took place in a purpose-built tunnel inside a farm, and after harvesting, a certain amount of mushrooms was dried and reduced to powder to proceed with the evaluation of antimicrobial activity against the multidrug-resistant bacterial strains Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, and Klebsiella pneumoniae. P. nebrodensis extract showed reduction of biofilm formation by up to 71% for S. aureus and by 18% for Ps. aeruginosa compared to the untreated control. The results suggest that while the P. nebrodensis cold water extract does not exert direct antibacterial activity, it may interfere with biofilm formation, particularly in S. aureus, highlighting its potential as an anti-virulence agent. Besides, in both Ps. aeruginosa and S. aureus, treatment with the P. nebrodensis extract resulted in a reduction in biofilm formation compared to the untreated control. The potential of P. nebrodensis extracts in inhibiting biofilm formation processes by bacteria could lead to the discovery of new chemicals for use in clinical settings.